Growth and development of lepisanthes alata (blume) leenh fruit - Megat Muhammad Hatim, Megat Ahmad Yusuf (2015)
Growth and development of fruit is crucial to identify the characterstic changes during harvesting time of the fruit. The information on the growth and development, physico-chemical and the phytochemical properties of Lepisanthes alata during maturation are still lacking. Therefore, a study to determine growth and development characteristic changes of Lepisanthes alata was carried out. The fruits were harvested at different time for every two weeks of interval and the determination of physical properties (weight and density, length and diameter, peel color and firmness) and chemical changes (soluble solids concentration, titratable acidity, pH value, ascorbic acid) properties were carried out. The experiment was performed using completely randomize design (CRD). The collected data was analysed using Duncan’s multiple range test. The results indicated that the fruits had increased in size (length, diameter, weight and density), soluble solids concentration and pH. Results also show decreased in titratable acidity content and ascorbic acid content as the fruit grew and developed.